2010
DOI: 10.2174/1568210202017840096
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of the Sodium Iodide Symporter and its Potential for Targeted Gene Delivery

Abstract: The sodium iodide symporter (NIS) is responsible for thyroidal, salivary, gastric, intestinal and mammary iodide uptake. It was first cloned from the rat in 1996 and shortly thereafter from human and mouse tissue. In the intervening years, we have learned a great deal about the biology of NIS. Detailed knowledge of its genomic structure, transcriptional and post-transcriptional regulation and pharmacological modulation has underpinned the selection of NIS as an exciting approach for targeted gene delivery. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 143 publications
(244 reference statements)
0
10
0
Order By: Relevance
“…In its dual role as reporter and therapy gene, NIS allows direct, noninvasive imaging of functional NIS expression by 123 I scintigraphy and 124 I positron emission tomographic imaging as well as exact dosimetric calculations before proceeding to therapeutic application of 131 I or alternative radionuclides (Spitzweg and Morris, 2002;Dingli et al, 2003b;Hingorani et al, 2010). Our initial work in the prostate cancer model followed by several studies in a variety of tumor models have clearly demonstrated the enormous potential of NIS as one of the oldest and most successful targets of molecular imaging and radionuclide ( 131 I, 188 Re, 211 At) therapy (Spitzweg et al, 1999(Spitzweg et al, , 2000(Spitzweg et al, , 2007Kakinuma et al, 2003;Cengic et al, 2005;Dwyer et al, 2006a;Scholz et al, 2005;Willhauck et al, 2007Willhauck et al, , 2008a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In its dual role as reporter and therapy gene, NIS allows direct, noninvasive imaging of functional NIS expression by 123 I scintigraphy and 124 I positron emission tomographic imaging as well as exact dosimetric calculations before proceeding to therapeutic application of 131 I or alternative radionuclides (Spitzweg and Morris, 2002;Dingli et al, 2003b;Hingorani et al, 2010). Our initial work in the prostate cancer model followed by several studies in a variety of tumor models have clearly demonstrated the enormous potential of NIS as one of the oldest and most successful targets of molecular imaging and radionuclide ( 131 I, 188 Re, 211 At) therapy (Spitzweg et al, 1999(Spitzweg et al, , 2000(Spitzweg et al, , 2007Kakinuma et al, 2003;Cengic et al, 2005;Dwyer et al, 2006a;Scholz et al, 2005;Willhauck et al, 2007Willhauck et al, , 2008a.…”
Section: Discussionmentioning
confidence: 99%
“…The sodium iodide symporter (NIS) mediates the active transport of iodide across the basolateral membrane of thyroid cells and represents the molecular basis for the diagnostic and therapeutic application of radioiodine, which has been successfully used for more than 70 years in the treatment of patients with thyroid cancer (Spitzweg et al, 2001b;Hingorani et al, 2010). Since its cloning in 1996 NIS has been characterized as a novel promising target gene for the development of a novel gene therapy strategy based on selective NIS gene transfer into tumor cells followed by diagnostic and therapeutic application of radioiodine (Dai et al, 1996;Smanik et al, 1996;Spitzweg et al, 1999Spitzweg et al, , 2000Spitzweg et al, , 2001aSpitzweg et al, ,b, 2007Spitzweg and Morris, 2002;Kakinuma et al, 2003;Dingli et al, 2004;Cengic et al, 2005;Dwyer et al, 2005a;Scholz et al, 2005;Willhauck et al, 2007Willhauck et al, , 2008aTrujillo et al 2010;Hingorani et al, 2010;Li et al, 2010;Penheiter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning and characterization of the NIS gene have therefore allowed the development of the NIS gene therapy concept based on NIS gene transfer into nonthyroidal tumor cells, followed by diagnostic and therapeutic application of radioiodine (Dai et al, 1996;Smanik et al, 1996;Hingorani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…38 Other possible instances of false-positive results of iodine taken up by tissues other than in the normal biodistribution are inflammatory lung disease, gastrointestinal tract, salivary gland, and simple contamination. 39 In cases of dedifferentiated thyroid cancer, which may not be radioiodine avid, evaluation is also be possible using PET/ CT under withdrawal of thyroid hormone or Thyrogen stimulation. 40 Nuclear Medicine and Gender Differences in Brain Physiology…”
Section: Gender-focused Epidemiology In Thyroid Cancermentioning
confidence: 99%